Application of Clean and Healthy Lifestyle in Household Management of Coastal Communities - Grace Tedy Tulak; Yuhanah Yuhanah; Mohammad Syafar Sangkala (Media Kesehatan Masyarakat Indonesia, 2021)
The coastal area needs special attention regarding the health management for the people living there. Wowa Tamboli Village, Kolaka Regency, Southeast Sulawesi is one of the coastal areas that need attention in terms of health, especially for people who live in unhealthy houses. This study aimed to investigate the application of clean and healthy lifestyle in household management of coastal community. This type of research was descriptive with a total sampling technique of 354 households. The research instrument used a questionnaire consists of respondents characteristic and ten indicators of clean and healthy lifestyle. The results showed that the community had properly implemented clean and health lifestyle on indicators of exclusive breastfeeding, using clean water, washing hands with clean water and soap, eradicating house larvae, eating fruits and vegetables every day, and doing physical activity every day. However, it was still found that the head of the family has not fully implemented a clean and healthy lifestyle because the birth process was still assisted by traditional birth attendants (3.40%), who did not weigh the infant and toddler because of distance from health services (2.50%) and there were community members who still smoke in the house (25.40%). The application of a clean and healthy lifestyle in households is good in 7 indicators. However, 3 indicators are still lack of application.